2017
DOI: 10.14202/vetworld.2017.743-747
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diarrhea activity of the aqueous root bark extract of Byrsocarpus coccineus on castor oil-induced diarrhea in Wistar rats

Abstract: Aim:The use of traditional medicine as an alternative source of cure for many ailments has played an important role in health care delivery in both developing and developed countries. Byrsocarpus coccineus Schum and Thonn (Connaraceae) is used in traditional medicine for treatment of various disease conditions, including diarrhea. The anti-diarrhea activity of the root bark aqueous extract of B. coccineus was investigated in this study.Materials and Methods:Acute toxicity evaluation of the aqueous extract of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…30 min after, the rats were individually placed in a cage with plain white paper covering the floor of the cage. Each animal was observed for 3 h for wet and dry feces and this was measured by the difference in initial and final weight of the paper with and without the excrements after 3 h period [25]. The percent inhibition was calculated from the total number of wet feces in the loperamide and MRBE treatment groups in relative to the control treated group.…”
Section: Castor Oil-induced Diarrhea In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 min after, the rats were individually placed in a cage with plain white paper covering the floor of the cage. Each animal was observed for 3 h for wet and dry feces and this was measured by the difference in initial and final weight of the paper with and without the excrements after 3 h period [25]. The percent inhibition was calculated from the total number of wet feces in the loperamide and MRBE treatment groups in relative to the control treated group.…”
Section: Castor Oil-induced Diarrhea In Ratsmentioning
confidence: 99%
“…30 min after, each animal was sacrificed and the abdomen opened. The distance travelled by the charcoal in the small intestine was measured and recorded [25].…”
Section: Gastrointestinal Motility Test In Ratsmentioning
confidence: 99%
“…Escherichia coli caused hemolysis in Rattus norvegicus that was attenuated by aqueous root back extract of Byrsocarpus coccineus. E. coli was eliminated from the intestine and other organs by the extract [65]. Chinchilla chinchilla breed of the rabbit had increased erythrocytes, PCV, and hemoglobin as compared with other breeds [66].…”
Section: Effects Of Therapeutic Agents On Erythrocytesmentioning
confidence: 99%
“…B. coccineus known as 'Amuje wewe or Ado kanti-kanti' is a scandent shrub and it is indigenous to Nigeria (West Africa). Studies have shown that the plant has anti-plasmodia [6], antimicrobial [7], and anti-diarrhea activity [8]. Fractions of B. coccineus have been reported to modulate cytochrome P450 (CYP) enzyme activity, cytokine production, and anti-proliferation in colon cancer cell lines [9].…”
Section: Introductionmentioning
confidence: 99%